2017
DOI: 10.1016/j.ijom.2017.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Immediate implant placement into fresh extraction sockets versus delayed implants into healed sockets: A systematic review and meta-analysis

Abstract: The aim of this systematic review and meta-analysis was to compare the survival rate of the implants and the peri-implant tissue changes associated with implants inserted in fresh extraction sockets and those inserted in healed sockets. This review has been registered at PROSPERO under the number CRD42016043309. A systematic search was conducted by two reviewers independently in the databases PubMed/MEDLINE, Embase, and the Cochrane Library using different search terms; articles published until November 2016 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
94
4
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 64 publications
(214 reference statements)
2
94
4
4
Order By: Relevance
“…Both report on single as well as multiple implants and found significantly lower implant survival following IIP. However, as stated by the authors, these findings should be interpreted with caution given a high risk of bias in terms of randomization, allocation and blinding (Mello et al., ). In addition, only implant survival, marginal bone loss and probing depth changes were evaluated.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Both report on single as well as multiple implants and found significantly lower implant survival following IIP. However, as stated by the authors, these findings should be interpreted with caution given a high risk of bias in terms of randomization, allocation and blinding (Mello et al., ). In addition, only implant survival, marginal bone loss and probing depth changes were evaluated.…”
Section: Introductionmentioning
confidence: 90%
“…Two recent systematic reviews have been published on the comparison of IIP in fresh extraction sockets with DIP in healed bone (Chrcanovic, Albrektsson, & Wennerberg, ; Mello et al., ). Both report on single as well as multiple implants and found significantly lower implant survival following IIP.…”
Section: Introductionmentioning
confidence: 99%
“…This result is also in line with those obtained in recent systematic reviews of immediate and earlyplaced implants mainly on alveoli with intact buccal plate, achieving successful values (between 94% and 98%) in spite of the different methodology applied. (Bassir et al, 2018;Chen et al, 2018;Cosyn et al, 2019;Mello et al, 2017;Weigl & Strangio, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, immediate implant placement after flap dental extraction with healing abutment and soft-tissue displacement in order to achieve a primary closure has been associated with a greater recession of soft tissues, supporting a restricted use of this technique for aesthetical reasons in the anterior sector (Hammerle, Araujo, Simion, & Osteology Consensus, 2012). However, these approaches have changed with time-in spite of the negative results of some studies on flap immediate implants in the anterior sector (Tonetti et al, 2017)-as it appears in systematic reviews showing very similar results with immediate, early or delayed implants (Bassir, El Kholy, Chen, Lee, & Intini, 2018;Cosyn et al, 2019;Mello et al, 2017;Weigl & Strangio, 2016). This also applies to infected sockets at extraction due to periodontal or pulp conditions (Chen, Zhang, Weigl, & Gu, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In healthy patients, a systematic review showed that implants placed immediately after tooth extraction are accompanied by a survival rate comparable to implants placement in healed sites [23,24]. Even though there are studies claiming that immediate implant placement leads to a decrease in survival rates [25], the use of immediate implant therapy in specific populations, as in this study, requires consideration because of the potential benefits like a decrease in prosthetic rehabilitation time and fewer surgical procedures, to be gained from the therapy. In addition, dental loss has a negative impact on patients' quality of life which further emphasizes the importance of adequate dental rehabilitation [26][27][28].…”
Section: Introductionmentioning
confidence: 99%